Contrary destinies : a century of America's occupation, deoccupation, and reoccupation of Haiti - Pamphile, Léon Dénius (University Press of Florida, 2015)
In this book, Leon Pamphile presents the story of the 100-year relationship between the United States and Haiti and chronicles the internal, external, and natural forces that have shaped the nation as it is today, keeping a balance between the realities faced by the people on the island and the global and transnational contexts that affect their lives.